Carbon quantum-dots(cqds)-titanium nanotubes(tnts) photocatalyst for co2 conversion to ch4 - Azrina, Abd Aziz; Nurnisa Aqilah, Mohd Rapidi; Ummi Aqila, Suhaimi (2021)
The abundance of carbon dioxide as greenhouse gas makes it potentially useful for chemical syntheses in order to recycling it into useful chemicals will become a more attractive alternative for industry. This study focuses on synthesize and characterize TNTs and CQDs via hydrothermal method. One of the common methods to achieve activation is via sample acts as photocatalyst to improve the conversion of carbon dioxide to methane through photocatalysis. TNTs is synthesis using a hydrothermal method meanwhile, for CQDs extracted from Watermelon Rinds is synthesis by facile hydrothermal m. Titanium dioxide nanoparticles are photocatalysts, which have the capability to use energy in light to catalyse reactions with other molecules at reduced temperatures. cylinders. As TNTs and CQDs were successfully synthesized and characterized by Transmission Electron Microscopy (TEM). The image results indicate that TNTs structure has an average diameter of 10.55 nm and form into thick particles of nanotube. Meanwhile image of CQDs shows the morphology of CQDs is approximately spherical and the average particle size is 48.68 nm.